Genetic study of diabetic retinopathy: recruitment methodology and analysis of baseline characteristics. (28th October 2013) - Kaidonis, Georgia; Abhary, Sotoodeh; Daniell, Mark; Gillies, Mark; Fogarty, Rhys; Petrovsky, Nikolai; Jenkins, Alicia; Essex, Rohan; Chang, John H; Pal, Bishwanath; Hewitt, Alex W; Burdon, Kathryn P; et al.
Abstract Background Diabetic retinopathy (DR) is a blinding disease of increasing prevalence that is caused by a complex interplay of genetic and environmental factors. Here we describe the patient recruitment methodology, case and control definitions, and clinical characteristics of a study sample to be used for genome‐wide association analysis to detect genetic risk variants of DR. Methods One thousand six hundred sixty‐nine participants with either type 1 (T1) or type 2 (T2) diabetes mellitus (DM) aged 18 to 95 years were recruited in Australian hospital clinics. Individuals with T2DM had disease duration of at least 5 years and were taking oral hypoglycaemic medication, and/or insulin therapy. Participants underwent ophthalmic examination. Medical history and biochemistry results were collected. Venous blood was obtained for genetic analysis. Results Six hundred eighty‐three diabetic cases (178 T1DM and 505 T2DM participants) with sight‐threatening DR, defined as severe non‐proliferative DR, proliferative DR or diabetic macular oedema were included in this analysis. Eight hundred twelve individuals with DM but no DR or minimal non‐proliferative DR were recruited as controls (191 with T1DM and 621 with T2DM). The presence of sight‐threatening DR was significantly correlated with DM duration, hypertension, nephropathy, neuropathy, HbA1C and body mass index. Diabetic macular oedema was associated with T2DM (P < 0.001), whereas proliferative DR was associated with T1DM (P < 0.001). Conclusions Adoption of a case‐control study design involving extremes of the DR phenotype makes this a suitable cohort, for a well‐powered genome‐wide association study to detect genetic risk variants for DR.